Genomic analysis of Inonotus hispidus provides insights into its medicinal properties and evolutionary dynamics - Dingbang Ding; Hua Wang; Jiajun Liang; Chao Su; Minjuan Zhang; Feng Jiao; Lijun Bao; Xia Wang (Scientific Reports)
Abstract Inonotus hispidus, a fungal species morphologically closely related to the medicinal genus Sanghuang,has garned considerable attention due to its potential health-prompting benefits. This study presents the whole-genome sequence of I. hispidus ZA-14, a monokaryotic strain isolated from wild fruiting bodies growing in Morus alba (hereinafter referred to as MA). The 37.68 Mb genome was assembled from 5771 Mb of raw data, resulting in 51 contigs with a GC content of 48.48%. A total of 8924 protein-coding genes were predicted, with 223 non-coding RNAs identified. The genome analysis revealed a high density of genes associated with secondary metabolite biosynthesis, including those involved in terpenoid, polysaccharide, and flavonoid pathways—key contributors to its medicinal attributes. Comparative genomic analysis with other related fungal species provided insights into the evolutionary dynamics and speciation of I. hispidus. The study also identified a significant enrichment of glycoside hydrolase family genes, suggesting a critical role in nutrient absorption and utilization. These findings enhance our understanding of the genetic basis of I. hispidus’s medicinal value and its evolutionary relationships, providing a foundation for future breeding.